Constitutional principles and values - Gonzalez Ojeda, Magdiel (2021)
The constitutional principles and values, as are indisputable expressions of legal and ethical categories, can not have an equal academic approach that they have written rules. Therefore, the study and application of constitutional norms first task involves the interpretation of those rules; because in addition to the provision contained therein lies axiológicos that behave as a system of values; for this reason, its observance requires a teleological interpretation because they are principles and values, its validity is also conditional on there is a legal sense that allows recognize; feeling, by the way, which should be generalized to the entire community. The only way to demonstrate the social relevance of the principles and constitutional values is through repeated experience through legal institutions. The legal principles play a foundational role and in some circumstances also apply interpretative regulations. Some legal rules contain legal assessments and regulatory plexus of all nations is guided by legal principles underlying it. The origin and nature of the study of the principles and constitutional values has determined the presence, especially, of two conceptions, certainly at odds: A doctrine is developed under the natural law and the other in a historical perspective called positivist. To all this conceptual framework this research jusfilosofica comprising one of the great themes of philosophy of law is limited. Justice as the supreme value of the right (or the other legal values) is considered as an object in itself and it is clear that this is an existing object beyond experience, it is metaphysical objects and therefore the answer to the principles and constitutional values, will only practical in the extent of its fall functionality.